Right/Left-Handed Leaky Rectangular Waveguide with Broadside Radiation Property - Xingying Huo; Zheng Li (International Journal of Antennas and Propagation, 2021)
When a leaky rectangular waveguide is used to realize the coverage of radio wave in the small confined spaces, there will be a shadow region, which influences the coverage performance. In this paper, the traditional leaky rectangular waveguide is improved according to the principle of the equivalent circuit, by cutting interdigital slots in the upper wall and adding uniserial metal vias between the upper and lower walls of the rectangular waveguide. Thus, the right/left-handed transmission line property is introduced to the periodic leaky-waveguide (LWG), realizing the broadside radiation with relatively high gain (15.7 dBi), good cross polarization (−50 dB), and narrow half-power beamwidth (10.9°) at 6.97 GHz and providing a method for a uniform coverage of the radio wave in rooms without a shadow region.